What Explains Remittance Fees? : Panel Evidence - Beck, Thorsten; Janfils, Mathilde; Kpodar, Kangni (Washington, D.C. : International Monetary Fund, 2022)
This paper uses data across 365 corridors to document time and country variation in remittance fees and explore factors predicting variation in remittance fees. We document a general reduction in such fees over the past decade although the goal of fees below 3 percent has not been met yet in many corridors. We identify both cost- and risk-based constraints and market structure as barriers to lower remittance fees. Higher transaction costs as result of a more rural population in the sending country and lower scale are associated with higher remittance fees. However, lower risks due to the stability of fixed exchange rates and Internet rather than cash payment are associated with lower remittance fees. Finally, remittance corridors dominated by banks and few players are characterized by higher fees.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Access To Financial Services; Economics; Macroeconomics; Migration; Remittances